QUILOMBOLA SCHOOL EDUCATION AND GEOGRAPHY TEACHING AT VILA NOVA JUTAI - BREU BRANCO - PA - Santos, Robson Alves dos; Paixao, Karleison Coelho da; Santos, Luciano Laurindo dos; Araujo, Amarildo Silva; Ribeiro Rocha, Carlos Eduardo [UNESP]; Mariano de Souza, Marcus Vinicius (Univ Federal Fluminense, 2022)
In a country characterized by ethnic-racial diversity, with a large legacy of prejudice and basic rights denial, the projection of an alternative, affirmative teaching is made necessary, one that intertwines historical and everyday knowledge and that develops new critical stances out of quilombola voices, which are almost always silenced. This paper approaches formal school education, specifically Geography teaching in school education at the remaining quilombola community of Vila Nova Jutai, at the Breu Branco municipality, in Para (PA) state, Brazil. Thus, the project Nos Propomos (We Propose), developed at the community's school, sought to identify which were the main sociospacial issues within the community. The research was based on bibliographical surveys, project execution, questionnaires and an interview survey. Geography, as a science and a school subject, has a historical legacy of contributing to citizenship building processes through the critical analysis skills it develops among students about geographical space, giving them the opportunity to better understand sociospacial dynamics and changes.
Keywords: Culture; Territorialities; Quilombolas; Education